Comparative analysis between the gold standard titration method and a mathematical formula to predict CPAP pressure - Cíntia Felicio Adriano Rosa; Adriane Iurck Zonato; Ordival Augusto Rosa (Brazilian Journal of Otorhinolaryngology)
Objective: One lower-cost alternative to either manual or APAP titration is predicting therapeutic pressure by using mathematical formulas. This study aimed to determine whether the Miljeteig and Hoffstein predictor formula was equivalent to the pressure established by manual titration in a sleep laboratory in patients using nasal or pillow masks. Methods: The authors analyzed all CPAP titration polysomnography studies in adult patients for three consecutive months (May 20th to August 19th, 2018) in a sleep-disorders clinic. CPAP pressures were manually titrated over the night. Anthropometric data (age, sex, Body Mass Index [BMI], Neck [NC] and waist circumference) and polysomnographic data were documented. We tested Miljeteig and Hoffstein model formula-predicted CPAP (Hpred) accuracy in our patients, comparing formula results to our manual titration; Hpred = (0.16 BMI) + (0.13 NC) + (0.04 AHI) - 5.12. Results: Nasal masks were used in 55% of our patients (n = 86) and pillow masks in 45% (n = 71). There was no difference between groups for age, body mass index, neck circumference, waist circumference, gender, baseline apnea-hypopnea index, CPAP pressure and residual AHI during titration polysomnography. The mean difference obtained between CPAP pressure and Hpred formula was 2.4 cm H2O. The CPAP pressure means during titration was 2.4 cm H2O higher than pressure obtained by a formula for pillow group and 2.3 for the nasal group. Conclusions: In most patients, formula underestimated the CPAP pressure obtained during titration for both nasal and pillow masks. Even though the pressure is underestimated, this approach could help to define minimum and maximum titration pressure using APAP in patients with OSA until the optimal pressure can be determined in the sleep laboratory if necessary. Level of evidence: Level 3.